Aripiprazole use as a cause of dopamine agonist failure in the treatment of prolactinomas - Edward Mignone; Alistair K Jukes; Rowan Valentine; Richard Allison; Sunita M C De Sousa (Endocrine Oncology, 2025)
Prolactinomas are the most common hypersecretory pituitary adenoma. The traditional first-line therapy is dopamine agonists (DAs), which are highly effective and tolerated in the majority of cases. However, DAs have the potential for psychiatric complications, such as psychosis, impulse control disorders and anxiety/depression. It has been repeatedly suggested that aripiprazole may be considered in individuals with a psychiatric disorder and prolactinoma, potentially enabling DA dose reduction or even cessation. We report the first case of aripiprazole competing with cabergoline and reducing its efficacy in the treatment of a giant prolactinoma, as evidenced by an immediate and marked rise in serum prolactin (approximately 350% increase over 5 weeks) despite stable cabergoline dosing. We also present a systematic review of aripiprazole use in prolactinomas, showing that aripiprazole monotherapy effectively reduces serum prolactin and concurrently commenced aripiprazole/DA dual therapy may still permit prolactin lowering, although there were no previous cases where aripiprazole was added to an established DA therapy to indicate the direct effect of aripiprazole on DA efficacy. Based on our case, we support close monitoring of individuals with prolactinomas on dual aripiprazole/DA therapy and recommend against the addition of aripiprazole to DA therapy where timely prolactinoma treatment is essential (e.g. aggressive prolactinomas and those associated with compressive effects).